Knowledge and practices regarding pharmacoeconomics among resident doctors in a tertiary care teaching hospital - A. R., Reshma Raj; Sudha, M. J.; Viveka, S. (International Journal of Basic & Clinical Pharmacology, 2020)
Background: With skyrocketing health care costs, even the essential care provided by the health care service providers need to be evaluated under the lens. The development of nationwide awareness of cost-benefit, cost-utility and cost-effectiveness of services is the need of the hour. The objectives of the present study were to assess the knowledge about pharmacoeconomics among resident doctors and to assess the clinical application of pharmacoeconomics among them. Methods: A cross sectional questionnaire-based survey was conducted among resident doctors involving both interns and post-graduates of a teaching medical college. There were 20 questions; initial ten were for knowledge assessment and next ten questions assessed practical applications. Questions assessed the knowledge regarding components of pharmacoeconomics, direct and indirect medical costs, and application of pharmacoeconomics, local cost-effectiveness decisions and advantages of pharmacoeconomics. Results: Of the 118 participants who took part in the study, 42 were clinicians working in medical college hospital, 12 were clinicians working in dental college hospital, 24 medial postgraduates, 30 dental postgraduates and 10 interns. Nearly 90% of the respondents opine that concepts of pharmacoeconomics are not followed in every teaching hospital in India. Many participants (90%) opined that health economics and pharmacoeconomic are different. Nearly 94% of participants have not under gone any training regarding pharmacoeconomics. More than 95% respondents have opined that principles of pharmacoeconomics has to be introduced into current medial undergraduate curriculum. Conclusions: This study shows light on the knowledge and practices of resident doctors regarding principles of pharmacoeconomics. This study has revealed the level of awareness of younger generation regarding pharmacoeconomics.